Feminist Science Fiction and Feminist Epistemology - Calvin, Ritch. author. aut Link
XI, 304 p.
Keywords: This book argues that feminist science fiction shares the same concerns as feminist epistemology—challenges to the sex of the knower, the valuation of the abstract over the concrete, the dismissal of the physical, the focus on rationality and reason, the devaluation of embodied knowledge, and the containment of (some) bodies. Ritch Calvin argues that feminist science fiction asks questions of epistemology because those questions are central to making claims of subjectivity and identity. Calvin reveals how women, who have historically been marginal to the deliberations of philosophy and science, have made significant contributions to the reconsideration and reformulation of the epistemological models of the world and the individuals in it.